Simulation of a long term atmospheric corrosion process on plain and weathering steels (2003)
ABSTRACT: Information on weathering steel behaviour and its rust products characteristics after decades of atmospheric exposure are scarce. On the other side, generally accepted laboratory tests for the assessment of its corrosion resistance have not been developed yet. Consequently, simulating corrosion in the laboratory during long periods of time are attractive for the interesting and complete information obtainable from them. In the present work, AISI-SAE 1008 and ASTM'588 B steel samples have been exposed for two years to a immersion-emersion CEBELCOR type test in the laboratory, simulating a moderate urban atmosphere. Two groups of six samples each were tested. After the first year, three samples of each batch were retired for analysis and the rest was kept until they reached two years of exposure. The half cell electrode potentials were measured daily. The rust was characterized by metallographic techniques, Mossbauer spectroscopy (MS), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). Comparison was done with field exposure experiments reported in the literature, and conclusions on the behaviour of tested samples were drawn looking for differences and similarities with samples and structures under actual atmospheric conditions.